An Intelligent Engineering Based Water Treatment Injection Portable Type for Drinking Water Fulfilment in Disaster Conditions (Engineering Design) - Mulyono, Rifai Agung; Sapta, Wibowo Ady; Aditama, Wiwit (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In times of disaster, water is a natural resource crucial for preserving human life and other life forms. Access to water during a disaster is crucial, especially for drinking, cooking, and maintaining hygiene in refugee camps. It also helps to stop the spread of water-borne diseases. Typical issues include cloudy water, damage to the piping installation system and water treatment, issues with the water distribution system, and a lack of water in evacuation shelters and evacuation areas. Activated charcoal, silica sand, and zeolite media were used in this study to test the efficacy of Portable Injection-Type Water Treatment by evaluating physical, chemical, and microbiological parameters. A pretest-posttest research design characterizes the experimental nature of this study. After filtering river water samples, the following parameters were measured: turbidity, TDS, pH, iron (Fe), manganese (Mn), and the MPN (Most Probable Number) Index of Coliform and E. coli. For data analysis in this study, the T-test is used. The findings of this study demonstrate the ability of portable injection with a triple-up flow device in filtration to obtain a percentage of reduced water quality, with a yield of 78.3% water turbidity, 19.5% dissolved solids, 1.62% pH level, 21.61% organic matter, water hardness content of 10.7%, Coliform 83.99%, E. coli 95.19%. Analysis using the T-test yielded a p-value<α, so statistically, there were differences in river water parameters before and after using the Portable Injection tool.